Sex differences in 90-day outcomes after mechanical thrombectomy for acute ischemic stroke. (10th August 2018) - Madsen, Tracy E; DeCroce-Movson, Eliza; Hemendinger, Morgan; McTaggart, Ryan A; Yaghi, Shadi; Cutting, Shawna; Furie, Karen L; Saad, Ali; Siket, Matthew S; Jayaraman, Mahesh V
Abstract : Background: It is largely unknown whether functional outcomes after mechanical thrombectomy for large vessel occlusion (LVO) ischemic strokes differ by sex in non-clinical trial populations. We investigated sex differences in 90-day outcomes among ischemic stroke patients receiving mechanical thrombectomy. Methods: This was a prospective cohort of adults treated with mechanical thrombectomy for LVO at a single academic comprehensive stroke center from July 2015 to April 2017. Data on independence (mRS ≤2) at hospital discharge and 90 days were collected prospectively. Multiple logistic regression was used to determine the association between sex and 90-day independence, first adjusting for demographics, pre-stroke mRS, and NIHSS, then by co-morbidities and time to thrombectomy, and finally by vessel recanalization and use of intravenous thrombolysis. Results: We included 279 patients, 52% of whom were female. Compared with males, females were older (median years (IQR) 81 (75–88) vs. 71.5 (60–81), P<0.001) and had higher baseline NIHSS (mean SD 18.2±7.5 vs . 16.0±7.1, P=0.02). Similar proportions of males and females had pre-stroke mRS ≤2 (73.3% vs.67.1%, P=0.27). In multivariate analyses, males and females had a similar likelihood of being independent at discharge (aOR 0.71 (95%CI 0.32 to 1.58)), but females were less likely to be independent at 90 days (aOR 0.37 95% CI 0.16 to 0.87). Conclusions: In patients treated with mechanical thrombectomy for LVOs at a large comprehensive stroke center, females were less likely to be independent at 90 days. Future research should investigate contributors to poor outcomes post-discharge in females with LVOs, along with potential interventions to improve outcomes.